A highly stable bifunctional catalyst based on 3D Co(OH)2@NCNTs@NF towards overall water-splitting. (May 2018) - Guo, Pan; Wu, Jian; Li, Xi-Bo; Luo, Jun; Lau, Woon-Ming; Liu, Hao; Sun, Xue-Liang; Liu, Li-Min
Abstract: Electrocatalysts with low overpotential and high stability are highly demanded in water-splitting system. The efficiency of water-splitting is largely restricted by the oxygen evolution reaction (OER). Here, we developed a two-step method to prepare 3D porous material through chemical vapor deposition and electrodeposition combined with the first-principles calculations. Ultrathin α-Co(OH)2 nanosheets grown on the combined substrate of N-doped carbon nanotubes (NCNTs) and nickel foam were fabricated to investigate their electrochemical behaviour. Because of the characteristics of the ultrathin, microporous α-Co(OH)2 and its derivatives, the 3D Co(OH)2 @NCNTs@NF exhibits outstanding performance as a bifunctional catalyst for water-splitting. The overpotentials to achieve 10 mA cm −2 current density in 1 M KOH for OER and hydrogen evolution reaction (HER) are 270 mV and 170 mV, respectively. The as-prepared material exhibits superior stability, which generate 10 mA cm −2 current density in overall water-splitting over 600 h without obvious degradation in 1 M KOH at voltage of 1.72 V vs. RHE. The first-principles calculations reveal that the N-doping not only can effectively enhance the interaction between the substrate and active material (CoOOH), but also modulate the electronic structure of CoOOH to speed up the O2 releasing during the OER. Graphical abstract: fx1 Highlights: 3D binder-free catalyst was prepared by CVD and electrodeposition. The Co(OH)2 @NCNTs@NF possesses open porous structure. The Co(OH)2 @NCNTs@NF exhibits high activity and stability in water-splitting.